1985
DOI: 10.1007/bf00953994
|View full text |Cite
|
Sign up to set email alerts
|

Tight junctional permeability of the resting and carbachol stimulated exocrine rabbit pancreas

Abstract: The permeability of the pancreatic epithelium to horseradish peroxidase is investigated in the resting and carbachol stimulated rabbit pancreas. Horse radish peroxidase administered to the bathing medium of the isolated rabbit pancreas appears in the secreted fluid of the pancreas in a relatively low concentration. Carbachol stimulates both protein secretion and the passage of horse radish peroxidase into the secretory fluid. Histochemical assessment shows that horseradish peroxidase enters the interstitial sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…For example, vasopressin, epinephrine, and angiotensin increase TJ permeability in perfused rodent liver . A similar effect is observed in pancreas in response to cholinergic stimulation . Two general mechanisms for regulation of TJ permeability have been proposed.…”
mentioning
confidence: 88%
“…For example, vasopressin, epinephrine, and angiotensin increase TJ permeability in perfused rodent liver . A similar effect is observed in pancreas in response to cholinergic stimulation . Two general mechanisms for regulation of TJ permeability have been proposed.…”
mentioning
confidence: 88%
“…The barrier function controls the paracellular passage of solutes, ions, and various molecules. The structure of tight junctions in pancreatic exocrine and duct epithelial cells is dynamic and can be disrupted by, for example, carbachol and ductal hypertension [2224]. Disruption of tight junctions unseals the paracellular spaces of adjacent cells, leading to unlimited movement of solutes, etc., into and out of the paracellular spaces, so causing edema and diarrhea [21].…”
Section: Introductionmentioning
confidence: 99%
“…Kuijpers et al 9 reported a slight decrease in the number of strands and the depth of TJ in carbacholstimulated acinar cells. We also observed a decrease in the area and number of strands in the 20-IH and SS groups.…”
Section: Discussionmentioning
confidence: 98%
“…7,9,11,12,16,19 Correlation between the number of strands and paracellular electrical resistance or solute reflux impedance was also investigated. 18 Physiological analysis 19 showed a decreased number of strands and a barrier defect in inflamed colonic mucosa in patients with ulcerative colitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation